Notes on domestic violence against women:: a psychosocial analysis in pandemic times - Carneiro, Maiana Parente Gomes (2022)
This study addresses domestic violence against women in the period of the COVID-19 pandemic. The objective is to discuss the psychosocial implications related to the increase of domestic violence against women in the pandemic period. It was adopted as method the qualitative explanatory-exploratory research, of documentary nature, focusing on journalistic articles from the mapping of macro-region. The results indicated 6 categories of 15 journalistic articles: Domestic Violence; Feminicide; Crime Subnotification; Violence Increase; Psychosocial Impacts of the Pandemic in Domestic Violence; Public Politics Assistance. The present study considered the upsurge of domestic violence in the face of social isolation, as well as the role of public policies that through the scenario did not show to be formulaic in an intersectoral aspect.